Low-shrinkage styrene thermoplastic elastomer and preparation method thereof
By combining nano calcium carbonate with hyperbranched polysilane, the problem of poor flame retardant performance of styrene-based thermoplastic elastomers in the prior art is solved, and the effect of reducing shrinkage and improving flame retardant performance is achieved, and the scope of application is broadened.
Patent Information
- Application Number
- CN202411953069.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The styrene-based thermoplastic elastomers prepared in the prior art have poor flame retardant performance, which limits its application range.
Modified nano-calcium carbonate is used to modify the surface through hyperbranched polysilane, combined with styrene ethyl trimethoxysilane, borate-based siloxane and nitrogen-phosphorus-based siloxane, to improve the dispersion and compatibility of nano-calcium carbonate, thereby reducing the shrinkage rate of styrene-based thermoplastic elastomers and improving their flame retardant properties.
It effectively reduces the shrinkage rate of styrene-based thermoplastic elastomers, significantly improves their flame retardant properties, and broadens their application range.
Smart Images

Figure BDA0005215291570000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermoplastic elastomers, and in particular relates to a low-shrinkage styrene-based thermoplastic elastomer and a preparation method thereof. Background Art
[0002] Thermoplastic elastomer is a polymer material that is highly elastic at room temperature and can be plasticized and formed at high temperature. It is called the "third generation rubber". It is abbreviated as TPE in English. According to its composition structure, it can usually be divided into the following categories: styrene thermoplastic elastomer, polyolefin thermoplastic elastomer, polyurethane thermoplastic elastomer, etc. Styrene thermoplastic elastomer mainly refers to thermoplastic elastomer prepared with SBS and SEBS as raw materials, among which SEBS is a thermoplastic rubber synthesized by block copolymerization of styrene and butadiene. The SEBS structure contains styrene rigid chain segments that are in a glassy state at room temperature, giving the material a fixed shape and ensuring performance; the material structure contains butadiene flexible chain segments that are in a highly elastic state at room temperature, giving the material a comfortable soft touch and elasticity.
[0003] At present, there are many cases of styrene-based thermoplastic elastomer materials in automotive interior decoration parts. However, most thermoplastic elastomer materials are rarely used in occasions where high dimensional precision is required in automotive interior decoration parts. In order to adapt to the application of thermoplastic elastomers in some occasions where high dimensional precision is required, it is necessary to prepare a styrene-based thermoplastic elastomer with low shrinkage.
[0004] Patent announcement number CN108250653B discloses a thermoplastic elastomer composition and a molded product made therefrom. The patented thermoplastic elastomer composition comprises: styrene block copolymer, oil, polyolefin resin, polystyrene resin and inorganic filler. The shrinkage rate of the thermoplastic elastomer is reduced by a reasonable ratio. However, the styrene thermoplastic elastomer prepared by the patent and the prior art still has the disadvantage of poor flame retardancy, which limits the application scope of the styrene thermoplastic elastomer. Summary of the invention
[0005] In order to solve the problem that the styrene thermoplastic elastomer prepared by the prior art in the background technology still has the disadvantage of poor flame retardancy, which limits the application scope of the styrene thermoplastic elastomer, the purpose of the present invention is to provide a low shrinkage styrene thermoplastic elastomer and a preparation method.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] In a first aspect, the present invention provides a low shrinkage styrene-based thermoplastic elastomer, comprising the following raw materials in parts by weight: 20-30 parts of styrene-butadiene block copolymer, 10-20 parts of polystyrene resin, 30-40 parts of softening operating oil, 30-60 parts of modified nano calcium carbonate, 1-2 parts of lubricating dispersant, and 1-2 parts of antioxidant.
[0008] The modified nano calcium carbonate is nano calcium carbonate grafted with hyperbranched polysilane, and the hyperbranched polysilane is obtained by hydrolysis and condensation of styrylethyltrimethoxysilane, borate-based siloxane and nitrogen-phosphorus-based siloxane.
[0009] Further, the styrene-butadiene block copolymer is one or more of a styrene-butadiene-styrene block copolymer, a styrene-ethylene-butylene-styrene block copolymer, and a styrene-ethylene-propylene-styrene block copolymer.
[0010] Furthermore, the polystyrene resin is one or more of general-purpose polystyrene and high-impact polystyrene.
[0011] Furthermore, the softening process oil has a flash point greater than 200°C and a kinematic viscosity greater than 50 mm at 40°C. 2 / s of one or more of paraffin oil, cycloparaffin oil, aromatic oil, and straight-chain paraffin oil.
[0012] Furthermore, the lubricating dispersant is one or more of erucamide, oleamide, zinc stearate, magnesium stearate, silicone, and polyethylene wax.
[0013] Furthermore, the antioxidant is one or more of the hindered phenol antioxidant Irganox 1010, the phosphite antioxidant IRGAFOS168, and the amine antioxidant A.
[0014] Furthermore, the preparation method of modified nano calcium carbonate is:
[0015] Add nano calcium carbonate, acetic acid aqueous solution and tetrahydrofuran into a flask, control the temperature at 70-75° C., add a hyperbranched monomer, keep the temperature for reaction for 24 hours, wash with distilled water, and vacuum dry at 50-55° C. for 72 hours to obtain modified nano calcium carbonate.
[0016] The mass ratio of nano-calcium carbonate, acetic acid aqueous solution, tetrahydrofuran and hyperbranched monomer is 0.2:1:(6-10):2, the mass fraction of acetic acid aqueous solution is 66.7%, and the hyperbranched monomer is composed of styrylethyltrimethoxysilane, borate-based siloxane and nitrogen-phosphorus-based siloxane in a mass ratio of 1:0.2-0.4:0.6-0.8.
[0017] As an inorganic filler, nano calcium carbonate can effectively fill between the molecular chains of styrene thermoplastic elastomers and increase the volume fraction of the polymer matrix. This filling effect can limit the free movement of polymer molecular chains during processing and curing, thereby reducing the overall shrinkage caused by molecular chain shrinkage.
[0018] Nano calcium carbonate surface presents strong polarity, is usually incompatible with polymer material, this can form effective interface layer between nano calcium carbonate and polymer, makes nano calcium carbonate dispersibility bad, is unfavorable for nano calcium carbonate to play its role.In the above-mentioned reaction, the methoxyl group in hyperbranched monomer is hydrolyzed, generates silanol, then with the hydroxyl on nano calcium carbonate surface by hydrogen bonding, last dehydration condensation, the remaining hydroxyl on silanol is dehydrated condensed with the silanol generated by the hydrolysis of hyperbranched monomer again, repeats dehydration condensation reaction, finally forms hyperbranched structure, obtains modified nano calcium carbonate.Hyperbranched structure forms a deck "protective layer" on nano calcium carbonate surface, and this deck protective layer has certain steric hindrance effect.Steric hindrance effect can stop direct contact and reunion between nano calcium carbonate particles, thereby improves its dispersibility, and reduces the shrinkage of styrene thermoplastic elastomer. Hyperbranched polysilane can also reduce the surface free energy of nano-calcium carbonate. The reduction of surface free energy helps to disperse and stabilize nano-calcium carbonate in the organic phase, improves its compatibility and interfacial bonding with organic materials, and further reduces the shrinkage of styrene-based thermoplastic elastomers.
[0019] Further, the preparation method of borate siloxane is:
[0020] Add trans-1-propene-1-ylboronic acid and 3-mercaptopropyltrimethoxysilane to tetrahydrofuran, mix well, then add benzoin dimethyl ether, stir for 1-2 hours, irradiate with ultraviolet light for 30-40 minutes at room temperature, remove the solvent by reduced pressure distillation after the reaction, precipitate in n-hexane three times, and vacuum dry at 30-40°C to constant weight to obtain borate siloxane.
[0021] The dosage ratio of trans-1-propene-1-ylboric acid, 3-mercaptopropyltrimethoxysilane, tetrahydrofuran and benzoin dimethyl ether is 0.84 g: 1.96 g: 14 mL: 0.05-0.08 g; the power of ultraviolet lamp irradiation is 20 W, and the wavelength is 365 nm.
[0022] In the above reaction step, under the action of the initiator benzoin dimethyl ether, the double bond of trans-1-propylene-1-boronic acid and the mercapto group in 3-mercaptopropyltrimethoxysilane undergo a mercapto-ene click reaction to obtain borate-based siloxane.
[0023] Furthermore, the preparation method of nitrogen-phosphorus-based siloxane is:
[0024] After the Schlenk bottle was closed and nitrogen was exchanged three times, it was protected with nitrogen and placed in a low temperature tank at -40°C. γ-aminopropyltriethoxysilane, triethylamine and toluene were injected into the Schlenk bottle in turn. After stirring for 10 minutes, diphenylphosphine chloride was slowly added dropwise, and the mixture was finished within 30 minutes. After stirring for 15 minutes, the mixture was removed from the low temperature tank and stirred at room temperature for 2.5 hours. The sand core funnel was filled with diatomaceous earth, and the generated triethylamine hydrochloride was removed by suction filtration. The Schlenk bottle and triethylamine hydrochloride were washed with toluene and n-hexane in turn. The filtrates were combined and the solvent was removed by rotary evaporation to obtain nitrogen-phosphorus-based siloxane.
[0025] The volume ratio of γ-aminopropyltriethoxysilane, triethylamine, toluene and diphenylphosphine chloride is 3.5:4.6:60:5.6.
[0026] In the above reaction steps, the amino group of γ-aminopropyltriethoxysilane undergoes a substitution reaction with the chlorine in diphenylphosphine chloride to obtain nitrogen-phosphorus-based siloxane, and triethylamine serves as an acid-binding agent in the reaction.
[0027] In a second aspect, the present invention provides a method for preparing a low shrinkage styrene-based thermoplastic elastomer, comprising the following steps:
[0028] (1) putting the styrene-butadiene block copolymer and softening process oil into a high-speed mixer in sequence, stirring at a speed of 300-500 r / min for 5-40 minutes, and standing for 24 hours for use; then putting the polystyrene resin, modified nano calcium carbonate, lubricant, and antioxidant into the high-speed mixer together, stirring at 100-300 r / min for 3-8 minutes, to obtain a premix semi-finished product;
[0029] (2) Add the semi-finished premix into an extruder, melt-extrude and granulate to obtain a low shrinkage styrene-based thermoplastic elastomer.
[0030] Furthermore, in step (2), the extruder is a co-rotating twin-screw extruder, the feed speed is 200-300 r / min, the screw speed is 300-500 r / min, and the screw aspect ratio is 52.
[0031] Furthermore, in step (2), the temperature of the first stage of melt extrusion does not exceed 170°C, and the temperature of the remaining stages is 190-250°C.
[0032] Beneficial effects of the present invention:
[0033] 1. When preparing styrene thermoplastic elastomer, modified nano calcium carbonate is added in the present invention, and nano calcium carbonate is surface-modified by hyperbranched polysilane, and hyperbranched polysilane is obtained by hydrolysis and condensation of styrylethyl trimethoxysilane, borate-based siloxane and nitrogen-phosphorus-based siloxane.Styrylethyl trimethoxysilane can make the surface of modified nano calcium carbonate contain styrylethyl structure, and this structure has certain similarity with the structure of polystyrene and styrene-butadiene block copolymer, thereby improving the compatibility of modified nano calcium carbonate and matrix, and then improving the mechanical property of styrene thermoplastic elastomer, reducing the shrinkage of styrene thermoplastic elastomer.Borate-based siloxane and nitrogen-phosphorus-based siloxane contain nitrogen, phosphorus, silicon, boron, sulfur multiple flame retardant elements, and these flame retardant elements can jointly improve the flame retardant property of styrene thermoplastic elastomer through synergistic effect. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Preparation Example 1
[0036] The preparation method of the borate-based siloxane of this preparation example is:
[0037] 0.84 g of trans-1-propene-1-ylboronic acid and 1.96 g of 3-mercaptopropyltrimethoxysilane were added to 14 mL of tetrahydrofuran, and the mixture was evenly mixed. Then, 0.05 g of benzoin dimethyl ether was added and stirred for 1 h. The mixture was irradiated with an ultraviolet lamp at room temperature for 30 min. The power of the ultraviolet lamp was 20 W and the wavelength was 365 nm. After the reaction, the solvent was removed by distillation under reduced pressure. The mixture was precipitated in n-hexane three times and dried in vacuum at 30 °C to constant weight to obtain borate siloxane.
[0038] Preparation Example 2
[0039] The preparation method of the borate-based siloxane of this preparation example is:
[0040] 0.84 g of trans-1-propene-1-ylboronic acid and 1.96 g of 3-mercaptopropyltrimethoxysilane were added to 14 mL of tetrahydrofuran, and the mixture was evenly mixed. Then, 0.08 g of benzoin dimethyl ether was added and stirred for 2 h. The mixture was irradiated with an ultraviolet lamp at room temperature for 40 min. The power of the ultraviolet lamp was 20 W and the wavelength was 365 nm. After the reaction, the solvent was removed by distillation under reduced pressure. The mixture was precipitated in n-hexane three times and dried in vacuum at 40 °C to constant weight to obtain borate siloxane.
[0041] Preparation Example 3
[0042] The preparation method of the nitrogen-phosphorus-based siloxane in this preparation example is:
[0043] After the Schlenk bottle was closed and nitrogen was exchanged three times, it was protected with nitrogen and placed in a -40°C low temperature tank. 3.5 mL of γ-aminopropyltriethoxysilane, 4.6 mL of triethylamine and 60 mL of toluene were injected into the Schlenk bottle in sequence. After stirring for 10 minutes, 5.6 mL of diphenylphosphine chloride was slowly added dropwise, and the mixture was finished within 30 minutes. After stirring for 15 minutes, the mixture was removed from the low temperature tank and stirred at room temperature for 2.5 hours. The sand core funnel was filled with diatomaceous earth, and the generated triethylamine hydrochloride was removed by suction filtration. The Schlenk bottle and triethylamine hydrochloride were washed with toluene and n-hexane in sequence. The filtrates were combined and the solvent was removed by rotary evaporation to obtain nitrogen-phosphorus-based siloxane.
[0044] Preparation Example 4
[0045] The preparation method of the modified nano calcium carbonate of this preparation example is:
[0046] 0.2g of nano calcium carbonate, 1g of 66.7% acetic acid aqueous solution, and 6g of tetrahydrofuran were added to a flask, the temperature was controlled at 70°C, 2g of hyperbranched monomer was added, the reaction was kept warm for 24h, washed with distilled water, and vacuum dried at 50°C for 72h to obtain modified nano calcium carbonate. The hyperbranched monomer is composed of styrylethyltrimethoxysilane, the borate-based siloxane prepared in Preparation Example 1, and the nitrogen-phosphorus-based siloxane prepared in Preparation Example 3 in a mass ratio of 1:0.2:0.8.
[0047] Preparation Example 5
[0048] The preparation method of the modified nano calcium carbonate of this preparation example is:
[0049] 0.2g of nano calcium carbonate, 1g of 66.7% acetic acid aqueous solution, and 8g of tetrahydrofuran were added to a flask, the temperature was controlled at 72°C, 2g of hyperbranched monomer was added, the reaction was kept warm for 24h, washed with distilled water, and vacuum dried at 52°C for 72h to obtain modified nano calcium carbonate. The hyperbranched monomer was composed of styrylethyltrimethoxysilane, borate-based siloxane prepared in Preparation Example 2, and nitrogen-phosphorus-based siloxane prepared in Preparation Example 3 in a mass ratio of 1:0.3:0.7.
[0050] Preparation Example 6
[0051] The preparation method of the modified nano calcium carbonate of this preparation example is:
[0052] 0.2g of nano calcium carbonate, 1g of 66.7% acetic acid aqueous solution, and 10g of tetrahydrofuran were added to a flask, the temperature was controlled at 75°C, 2g of hyperbranched monomer was added, the reaction was kept warm for 24h, washed with distilled water, and vacuum dried at 55°C for 72h to obtain modified nano calcium carbonate. The hyperbranched monomer was composed of styrylethyltrimethoxysilane, borate-based siloxane prepared in Preparation Example 2, and nitrogen-phosphorus-based siloxane prepared in Preparation Example 3 in a mass ratio of 1:0.4:0.6.
[0053] Comparative Example 1
[0054] Compared with Preparation Example 4, the only difference is:
[0055] The hyperbranched monomer is composed of styrylethyltrimethoxysilane and nitrogen-phosphorus-based siloxane in a mass ratio of 1:1.
[0056] Comparative Example 2
[0057] Compared with Preparation Example 4, the only difference is:
[0058] The hyperbranched monomer is composed of styrylethyltrimethoxysilane and borate siloxane in a mass ratio of 1:1.
[0059] Comparative Example 3
[0060] Compared with Preparation Example 4, the only difference is:
[0061] The hyperbranched monomer is styrylethyltrimethoxysilane.
[0062] Comparative Example 4
[0063] Compared with Preparation Example 4, the only difference is:
[0064] Use nano calcium carbonate directly.
[0065] Example 1
[0066] The present embodiment provides a low shrinkage styrene-based thermoplastic elastomer, comprising the following raw materials in parts by weight: 20 parts of styrene-butadiene block copolymer, 10 parts of polystyrene resin, 30 parts of softening operating oil, 30 parts of modified nano-calcium carbonate prepared in Preparation Example 4, 1 part of lubricating dispersant, and 1 part of antioxidant.
[0067] The styrene-butadiene block copolymer is a styrene-ethylene-propylene-styrene block copolymer with a styrene content of 31%, the polystyrene resin is a general-purpose polystyrene resin, and the softening operating oil is a resin with a flash point greater than 200°C and a kinematic viscosity greater than 50 mm at 40°C. 2 / s paraffin oil, the lubricant is a mixture of 30% erucamide and 70% zinc stearate, and the antioxidant is Irganox 1010.
[0068] The preparation method of the low shrinkage styrene thermoplastic elastomer is as follows:
[0069] (1) putting the styrene-butadiene block copolymer and the softening process oil into a high-speed stirrer in sequence, stirring at a speed of 400 r / min for 25 minutes, and standing for 24 hours for standby use; then putting the polystyrene resin, modified nano calcium carbonate, lubricant, and antioxidant into the high-speed stirrer together, stirring at a speed of 200 r / min for 6 minutes, to obtain a premix semi-finished product;
[0070] (2) Add the semi-finished premix to a co-rotating twin-screw extruder with a feed speed of 250 r / min, a screw speed of 400 r / min, and a screw aspect ratio of 52. Control the processing temperature of the plasticizing melting zone and the melt conveying zone. Use a vacuum pump to evacuate the tail section of the extruder. After melt extrusion and granulation by the extruder, the finished product is obtained. The first section temperature of the melt extrusion is set to 170°C, and the rest are 190°C / 190°C / 200°C / 200°C / 210°C / 210°C / 210°C / 200°C / 190°C / 190°C / 190°C.
[0071] Example 2
[0072] Compared with Example 1, the only difference is:
[0073] 22.5 parts of styrene-butadiene block copolymer, 12.5 parts of polystyrene resin, 32.5 parts of softening process oil, 37.5 parts of modified nano calcium carbonate prepared in Preparation Example 5, 1.25 parts of lubricating dispersant, and 1.25 parts of antioxidant.
[0074] Example 3
[0075] Compared with Example 1, the only difference is:
[0076] 25 parts of styrene-butadiene block copolymer, 15 parts of polystyrene resin, 35 parts of softening process oil, 45 parts of modified nano calcium carbonate prepared in Preparation Example 6, 1.5 parts of lubricating dispersant, and 1.5 parts of antioxidant.
[0077] Example 4
[0078] Compared with Example 1, the only difference is:
[0079] 27.5 parts of styrene-butadiene block copolymer, 17.5 parts of polystyrene resin, 37.5 parts of softening process oil, 52.5 parts of modified nano calcium carbonate prepared in Preparation Example 6, 1.75 parts of lubricating dispersant, and 1.75 parts of antioxidant.
[0080] Example 5
[0081] Compared with Example 1, the only difference is:
[0082] 30 parts of styrene-butadiene block copolymer, 20 parts of polystyrene resin, 40 parts of softening operation oil, 60 parts of modified nano calcium carbonate prepared in Preparation Example 6, 2 parts of lubricating dispersant, and 2 parts of antioxidant.
[0083] Comparative Example 1
[0084] Compared with Example 1, the only difference is:
[0085] The modified nano calcium carbonate prepared in Preparation Example 4 was replaced by the product in Control Example 1.
[0086] Comparative Example 2
[0087] Compared with Example 1, the only difference is:
[0088] The modified nano calcium carbonate prepared in Preparation Example 4 was replaced by the product in Control Example 2.
[0089] Comparative Example 3
[0090] Compared with Example 1, the only difference is:
[0091] The modified nano calcium carbonate prepared in Preparation Example 4 was replaced by the product in Control Example 3.
[0092] Comparative Example 4
[0093] Compared with Example 1, the only difference is:
[0094] The modified nano calcium carbonate prepared in Preparation Example 4 was replaced by the product in Control Example 4.
[0095] The performance tests were performed on the styrene thermoplastic elastomers prepared in Examples 1 to 5 and Comparative Examples 1 to 4. The test items are as follows, and the results are shown in Table 1:
[0096] 1. Shrinkage: The test standard is ASTM D955-2008.
[0097] 2. Tensile strength: The test standard is ISO 37-1, and the tensile test rate is 500mm / min;
[0098] 3. Elongation at break: The test standard is ISO 37-1.
[0099] 4. Flame retardant performance: Test the oxygen index of the sample according to GB / T 2406.2-2009.
[0100] Table 1
[0101]
[0102]
[0103] As can be seen from Table 1, the comprehensive performance of the styrene-based thermoplastic elastomers prepared in Examples 1 to 5 is better than that of Comparative Examples 1 and 4. Comparative Examples 1 and 2 contain only nitrogen-phosphorus-based siloxane and borate-based siloxane, which cannot synergistically perform flame retardant effects, so the flame retardant performance is reduced; Comparative Example 3 does not contain flame retardant elements, and the flame retardant performance is further reduced; the nano calcium carbonate in Comparative Example 4 is not subjected to hyperbranching treatment, and the dispersion performance is poor, and the final comprehensive performance is the worst.
[0104] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0105] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A low shrinkage styrene thermoplastic elastomer, characterized in that: The invention comprises the following raw materials in parts by weight: 20-30 parts of styrene-butadiene block copolymer, 10-20 parts of polystyrene resin, 30-40 parts of softening operating oil, 30-60 parts of modified nano calcium carbonate, 1-2 parts of lubricating dispersant, and 1-2 parts of antioxidant; The modified nano calcium carbonate is nano calcium carbonate grafted with hyperbranched polysilane, and the hyperbranched polysilane is obtained by hydrolysis and condensation of styrylethyltrimethoxysilane, borate-based siloxane and nitrogen-phosphorus-based siloxane.
2. The low shrinkage styrene-based thermoplastic elastomer according to claim 1, characterized in that: The styrene-butadiene block copolymer is one or more of a styrene-butadiene-styrene block copolymer, a styrene-ethylene-butylene-styrene block copolymer, and a styrene-ethylene-propylene-styrene block copolymer.
3. The low shrinkage styrene-based thermoplastic elastomer according to claim 1, characterized in that: The polystyrene resin is one or more of general-purpose polystyrene and high-impact polystyrene.
4. The low shrinkage styrene-based thermoplastic elastomer according to claim 1, characterized in that: The softening operating oil has a flash point greater than 200°C and a kinematic viscosity greater than 50 mm at 40°C. 2 / s of one or more of paraffin oil, cycloparaffin oil, aromatic oil, and straight-chain paraffin oil.
5. The low shrinkage styrene-based thermoplastic elastomer according to claim 1, characterized in that: The antioxidant is one or more of the following: hindered phenol antioxidant Irganox 1010, phosphite antioxidant I RGAFOS168, and amine antioxidant A.
6. The low shrinkage styrene-based thermoplastic elastomer according to claim 1, characterized in that: The preparation method of modified nano calcium carbonate is: Add nano calcium carbonate, acetic acid aqueous solution and tetrahydrofuran into a flask, control the temperature at 70-75°C, add a hyperbranched monomer, keep the temperature for 24 hours, wash with distilled water, and vacuum dry at 50-55°C for 72 hours to obtain modified nano calcium carbonate; The mass ratio of nano-calcium carbonate, acetic acid aqueous solution, tetrahydrofuran and hyperbranched monomer is 0.2:1:(6-10):2, the mass fraction of acetic acid aqueous solution is 66.7%, and the hyperbranched monomer is composed of styrylethyltrimethoxysilane, borate-based siloxane and nitrogen-phosphorus-based siloxane in a mass ratio of 1:0.2-0.4:0.6-0.
8.
7. The low shrinkage styrene-based thermoplastic elastomer according to claim 6, characterized in that: The preparation method of borate siloxane is: Add trans-1-propene-1-ylboronic acid and 3-mercaptopropyltrimethoxysilane to tetrahydrofuran, mix well, then add benzoin dimethyl ether, stir for 1-2 hours, irradiate with ultraviolet light for 30-40 minutes at room temperature, distill under reduced pressure after the reaction is completed, precipitate, and dry to constant weight to obtain borate siloxane; The dosage ratio of trans-1-propene-1-ylboric acid, 3-mercaptopropyltrimethoxysilane, tetrahydrofuran and benzoin dimethyl ether is 0.84 g: 1.96 g: 14 mL: 0.05-0.08 g; the power of ultraviolet lamp irradiation is 20 W, and the wavelength is 365 nm.
8. The low shrinkage styrene-based thermoplastic elastomer according to claim 6, characterized in that: The preparation method of nitrogen-phosphorus siloxane is: After the Schlenk bottle was closed and nitrogen was exchanged three times, it was protected with nitrogen and placed in a low-temperature tank at -40°C. γ-aminopropyltriethoxysilane, triethylamine and toluene were injected into the Schlenk bottle in sequence. After stirring for 10 minutes, diphenylphosphine chloride was slowly added dropwise, and the addition was completed within 30 minutes. After stirring for 15 minutes, it was removed from the low-temperature tank and stirred at room temperature for 2.5 hours. A sand core funnel was filled with diatomaceous earth, and suction was applied. After washing, the filtrate was combined and rotary evaporated to obtain nitrogen-phosphorus-based siloxane. The volume ratio of γ-aminopropyltriethoxysilane, triethylamine, toluene and diphenylphosphine chloride is 3.5:4.6:60:5.
6.
9. The method for preparing a low shrinkage styrene-based thermoplastic elastomer according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) putting the styrene-butadiene block copolymer and softening process oil into a high-speed mixer in sequence, stirring at a speed of 300-500 r / min for 5-40 minutes, and standing for 24 hours for use; then putting the polystyrene resin, modified nano calcium carbonate, lubricant, and antioxidant into the high-speed mixer together, stirring at 100-300 r / min for 3-8 minutes, to obtain a premix semi-finished product; (2) Add the semi-finished premix into an extruder, melt-extrude and granulate to obtain a low shrinkage styrene-based thermoplastic elastomer.
10. The method for preparing a low shrinkage styrene-based thermoplastic elastomer according to claim 9, characterized in that: In step (2), the extruder is a co-rotating twin-screw extruder, the feed speed is 200-300 r / min, the screw speed is 300-500 r / min, and the screw aspect ratio is 52; the temperature of the first section of melt extrusion does not exceed 170°C, and the temperature of the remaining sections is 190-250°C.
Citation Information
Patent Citations
Thermoplastic elastomer compositions and molded articles made therefrom
CN108250653B
Organic and inorganic hybrid microsphere particle, preparation and application thereof
CN104418990A
Impact-resistant plastic and preparation method thereof
CN116731430A
Method of rendering substrates water repellent using hyperbranched polymers containing silicon atoms
US5997954A
Cited By
Conductive unsaturated polyester resin and preparation method thereof
CN119978753A